Deležniški in deležijski skladi na -č in -ši v slovenščini - Jesenšek, Marko (Slavistična revija, 2006)
The Central Slovenian literary language between the 16th and 19th cc. did not make good use of the expression with participial and gerundival forms in -č and -ši, in fact, they were nearly forgotten. They were brought back to life in the 19th c. under the influence of the Prekmurje literary language and following the example of OCS. In the uniform Slovenian literary language of the second half of the 19th C., the forms in -č and -ši became fashionable and extremely literary, but at the end of the century with the arrival of the Slovenian Moderna they again retreated to the linguistic periphery, where they survive in expository and journalistic language as an effective syntactic condenser and means for the hierarchization of actions.
Keywords: deležja; deležnik; Eastern Slovenian language; gerunds; history of Slovene language; knjižni jezik; Old church Slavic; participals; skladnja; Slovene; Slovene grammar; Slovene language; Slovenian literary language; slovenska slovnica; slovenščina; standard language; stara cerkvena slovanščina; syntactic condensation; syntax; zgodovina jezika